2018
DOI: 10.1101/262162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated brain aging towards transcriptional inversion in a zebrafish model of familial Alzheimer’s disease

Abstract: AbstractAlzheimer’s disease (AD) develops silently over decades. We cannot easily access and analyse pre-symptomatic brains, so the earliest molecular changes that initiate AD remain unclear. Previously, we demonstrated that the genes mutated in early-onset, dominantly-inherited familial forms of AD (fAD) are evolving particularly rapidly in mice and rats. Fortunately, some non-mammalian vertebrates such as the zebrafish preserve fAD-relevant transcript isoforms of the Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 110 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…We found that large numbers of H3K27ac-defined enhancers were highly sensitive to the mitochondrial dysfunction resulting from rotenone exposure or TFAM KO. Among the TFs highlighted by motif analysis of upregulated H3K27ac peaks, the ZF factors ZNF264 and ZNF711 show a strong genetic association with neurological functions (Hin et al, 2018;van der Werf et al, 2017). AP-1, another enriched TF, reportedly promotes microglial neuroinflammation and DAergic neuron apoptosis in the SNpc (Tiwari and Pal, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that large numbers of H3K27ac-defined enhancers were highly sensitive to the mitochondrial dysfunction resulting from rotenone exposure or TFAM KO. Among the TFs highlighted by motif analysis of upregulated H3K27ac peaks, the ZF factors ZNF264 and ZNF711 show a strong genetic association with neurological functions (Hin et al, 2018;van der Werf et al, 2017). AP-1, another enriched TF, reportedly promotes microglial neuroinflammation and DAergic neuron apoptosis in the SNpc (Tiwari and Pal, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…5A). ZF proteins like ZNF264 contributed to the coordinated gene expression changes during brain aging (Hin et al, 2018) and ZNF711 is reportedly associated with mental retardation and cognitive disability (van der Werf et al, 2017). The DM family of TFs such as DMRT1 and DMRT3 were found to be involved in sexual development (Kopp, 2012).…”
Section: Characterization Of Genomic Enhancers Specific To Mitochondrmentioning
confidence: 99%
“…The mutant allele, Q96_K97del, of psen1 was a byproduct identified during our introduction of the K97fs mutation into psen1 (that models the K115fs mutation of human PSEN2 -see (8) for an explanation).…”
Section: Methodsmentioning
confidence: 99%
“…Genes differentially expressed between wild type and heterozygous mutant sibling fish were identified using moderated t-tests and a false discovery rate (FDR)-adjusted p-value cutoff of 0.05 as previously described (8,12,13). In total, 251 genes were identified as differentially expressed (see Additional File 1).…”
Section: Differentially Expressed Genes (De Genes)mentioning
confidence: 99%
“…Zebrafish are a versatile system in which to investigate, at the molecular level, the effects on the brain and other tissues of fAD mutations (29). The ability to generate large families of siblings and then raise these in a near identical environment (the same tank or the same recirculated-water system) can reduce genetic and environmental variability to allow more sensitive detection of mutation-dependent changes.…”
Section: Introductionmentioning
confidence: 99%